Development and evaluation of the US Healthy Food Diversity index. Issue 9 (16th September 2014) - Vadiveloo, Maya; Dixon, L. Beth; Mijanovich, Tod; Elbel, Brian; Parekh, Niyati
Abstract : Varied diets are diverse with respect to diet quality, and existing dietary variety indices do not capture this heterogeneity. We developed and evaluated the multidimensional US Healthy Food Diversity (HFD) index, which measures dietary variety, dietary quality and proportionality according to the 2010 Dietary Guidelines for Americans (DGA). In the present study, two 24 h dietary recalls from the 2003–6 National Health and Nutrition Examination Survey (NHANES) were used to estimate the intake of twenty-six food groups and health weights for each food group were informed by the 2010 DGA. The US HFD index can range between 0 (poor) and 1 − 1/ n, where n is the number of foods; the score is maximised by consuming a variety of foods in proportions recommended by the 2010 DGA. Energy-adjusted Pearson's correlations were computed between the US HFD index and each food group and the probability of adequacy for fifteen nutrients. Linear regression was run to test whether the index differentiated between subpopulations with differences in dietary quality commonly reported in the literature. The observed mean index score was 0·36, indicating that participants did not consume a variety of healthful foods. The index positively correlated with nutrient-dense foods including whole grains, fruits, orange vegetables and low-fat dairy ( r 0·12 to 0·64) and negatively correlated with added sugars and lean meats ( r − 0·14 to − 0·23). The index also positively correlated with the mean probability of nutrient adequacy ( r 0·41; P < 0·0001) and identified non-smokers, women and older adults as subpopulations with better dietary qualities. The US HFD index may be used to inform national dietary guidance and investigate whether healthful dietary variety promotes weight control.